Translation and Adaptation of the Spence Children’s Anxiety Scale (SCAS)-Parent Version at a Tertiary Level Hospital - Gurung, B.S.; Rana, M.; Shakya, S. (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: The study has examined the psycho-metric properties of the Nepali translation of SCAS-PV in terms of internal consistency and criterion validityMaterial and Method: Non probability sampling method was used. Participants were selected purposively under two groups of samples called clinical group and non clinical group. Study population of the study was the patient visiting outdoor and inpatient services of Department of Psychiatry and Mental Health, TUTH.Results: Among 200 (clinical= 98 and a non-clinical=102) sample of Nepalese children and adolescents. The specificity and sensitivity of the tool was assessed. Cronbach Alpha for the total scale (α =0.89), panic disorder (α =0.78), physical injury fear (α =0.72) and separation anxiety disorder (α =0.76) were of acceptable to good range. However, internal consistency of generalized anxiety disorder (α =0.67), obsessive compulsive disorder (α =0.59) and social anxiety disorder (α =0.68) were in questionable range. AUC statistic for total scale was in fair range, with optimum cut off score of 19.5 for the total scale with sensitivity of 65.3% and specificity of 64.7%.Conclusion: The study supports the utility of the SCAS-PV as a measure of anxiety symptoms in children. It can be used to directly compare symptom reporting across children in clinical. Because of the psychometric properties of the SCAS-PV that have been demonstrated in community and clinical samples, it is recommended that the SCAS-PV can be used in clinical and research contexts.